Volcanic-sedimentary sequence in the horizon “D” of condorsinga formation in alpamina (Morococha) - Ircañaupa Acevedo, Yber Juan (2018)
The lithology of the Alpamina area reveals that there was a small micro-basin in the site, the described lithology, analyzed and compared with the model described by J. Terrones (horizon “D”), for the, Morococha district , reveals great changes not only in the sedimentary phase but also in the volcanic phase of regular power (7m), of dacitic composition. This micro-basin that is located in the SE of the Morococha district is important to describe the events that occurred in the great Pucará basin, with its constant transgressions and regressions due to the subsidence processes. Processes that gave origin to very local emersions and submersions as in Alpamina or other regions.This sequence consists of intercalations of dolomites, sandstones and shales with a volcanic rock horizon of dacitic composition, all these strata have a similarity which is their small thickness, some only reach centimeters.